Genetic variants and molecular profiling of 46,XY gonadal dysgenesis using whole-exome sequencing - Zhang, Ning; You, Shuoming; Guo, Jingjing; Chang, Xingyu; Qiu, Junjun; Hua, Keqin (Frontiers in Endocrinology, 2025)
BackgroundMore than 60% of cases of 46,XY gonadal dysgenesis (GD), a condition classified as a disorder of sex development (DSD), remain unexplained, which is due to high genetic and clinical heterogeneity. Whole-exome sequencing (WES) is an efficient primary genetic diagnostic method; specifically, the use of WES in patients with 46,XY GD to explore the underlying genetic variants of the disorder may help us gain a deeper understanding of the pathogenesis and phenotype–genotype correlation of 46,XY GD.MethodsWe performed WES and pedigree studies to investigate the underlying genetic etiology of patients with 46,XY GD (six patients and six familial controls). The variants were confirmed via Sanger sequencing, and detailed functional prediction of the discovered genetic variants was conducted. Furthermore, we performed in-silico protein structural analysis and protein thermodynamic analysis to further explore the pathogenicity of these variants. GATA4 variants in patients with 46,XY GD with/without CHD and patients with cardiac disease alone were also analyzed.ResultsWe identified three novel pathogenic variants in GATA4:c.725G>C(p.Cys242Ser), NR5A1:c.370_380del(p.Pro124Glyfs*21), and DHX37:c.2020C>T(p.Arg674Trp), as well as one previously reported MAP3K1:c.1016G>A(p.Arg339Gln) variant. These variant sites are conserved among species and were predicted to be damaging according to functional algorithms and protein analyses. Additionally, 71.4% of the GATA4 amino acid changes in 46,XY GD were located in or close to the N-terminal zinc finger (N-ZF) domain. However, most GATA4 pathogenic variants (31.82%) in patients with isolated cardiac diseases were located in transactivation domain 1 (TAD1), and only 9.09% of the variants were located in the N-ZF domain.ConclusionThe N-ZF domain may play an exclusive role in the mechanism of GATA4 in the pathogenesis of 46,XY GD; therefore, this domain may be an interesting topic for future investigation. This study enhances our understanding of the genetic etiology and pathogenesis of 46,XY GD, which may aid in the diagnosis and intervention of this disorder.